Cyrano de Bergerac : heroic comedy in five acts - Rostand, Edmond, 1868-1918.; Bair, Lowell (New York : Signet Classic, 1972)
A new translation of the French drama set in seventeenth-century France telling of Cyrano de Bergerac's secret love for Roxane.
7.0.
7.0
Young Adult
Keywords: Cyrano de Bergerac, -- 1619-1655 -- Drama; Cyrano de Bergerac, -- 1619-1655 -- Drama; France -- History -- 17th century -- Drama; France -- History -- Drama